COVID-19, inflammatory response, iron homeostasis and toxicity: a prospective cohort study in the Emergency Department of Piacenza (Italy).: COVID19, Iron, Inflammation and Toxicity in ER - Duca, Lorena; Nava, Isabella; Vallisa, Daniele; Vadacca, Giovanni Battista; Magnacavallo, Andrea; Vercelli, Andrea; Capelli, Patrizio; Graziadei, Giovanna; Banchini, Filippo (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Dysregulation of iron metabolism and hyper-inflammation are two key points in the pathogenesis of coronavirus disease 2019 (COVID-19). Since high hepcidin levels and low serum iron can predict COVID-19 severity and mortality, we decided to investigate iron metabolism and inflammatory response in 32 COVID-19 adult patients with a diagnosis of COVID-19 defined by a positive result of RT-PCR nasopharyngeal swab, and admitted to an Italian emergency department for acute respiratory failure at different degree. Methods: Patients were stratified in 3 groups based on PaO2/FiO2 ratio at admission: 13 (41%) were normoxemic at rest and suffered from exertional dyspnea (group 1); 14 (44%) had a mild respiratory failure (group 2), and 5 (15%) a severe hypoxiemia (group 3). Results: White blood cells were significantly higher in group 3, while lymphocytes and hemoglobin were significantly reduced. Serum iron, transferrin saturation, non-transferrin-bound iron (NTBI) and ferritin were significantly increased in group 2. All the groups showed high hepcidin levels, but in group 3 this parameter was significantly altered. It is noteworthy that in group 1 inflammatory and oxidative indices were both within the normal range. Conclusions: We are aware that our study has some limitations, the small number of enrolled patients and the short period of data collection, but few works have been performed in the Emergency Room. However, we strongly believe that our results confirm the pivotal role of both iron metabolism dysregulation and hyper-inflammatory response in the pathogenesis of tissue and organ damage in COVID-19 patients.